Low Levels of Physical Activity and its Associations with Mood State, Daytime Sleepiness and Food Consumption in University Students - Fontanelli, Matheus de Souza; Correa, Gabriel Couto; Guiraldelli, Luciano Rogério; Mocelin, Aurenzo; Bertin, Renata Labronici; Ulbrich, Anderson Zampier (O Mundo da Saúde, 2024)
Starting a university course leads to significant changes in the student’s lifestyle and routine, with an impact on physical activity, mental health, sleeping habits and eating habits. The objective of the study was to verify the level of physical activity of young university students and its associations with mood, sleep quality and food consumption. This is a cross-sectional survey, carried out with university students studying Medicine at a Public Higher Education Institution. Anthropometric measurements, physical activity level (PAL) were assessed using the GT3x accelerometer (Actigraph), food consumption (24-hour inventory), and using the BECK and BRUMs / POMS questionnaires, health disorders were assessed. sleep and mood. Using SPSS software, comparative analysis was carried out with Student’s t test for independent groups, Pearson correlation inferential analysis and binary logistic regression. Of the university students analyzed (n=75), 54.7% (n=41) were male and, when compared to women, they had a higher physical activity level (PAL). Approximately 1/3 of the entire study sample performed less than 300 minutes of moderate/vigorous physical activity. The dietary profile of university students was not satisfactory. For both sexes, the POMS Total Score (Profile of Mood States) was found to be associated with university students who perform less than 300 minutes of physical activity per week. Women are 65% more likely to present with Tension Scale (POMS) when they are less active, and in men, the odds ratio is approximately three times greater for presenting Confusion (BRUMS - Brunel Mood Scale). It is concluded that the majority of university students on the course studied were insufficiently physically active and presented some changes in mood, daytime drowsiness and unsatisfactory food consumption.